Toxin ζ Triggers a Survival Response to Cope with Stress and Persistence - Moreno-del Álamo, María; Tabone, Mariangela; Lioy, Virginia S.; Alonso, Juan C. (Frontiers in Microbiology, 2017)
Bacteria have evolved complex regulatory controls in response to various environmental stresses. Protein toxins of the zeta superfamily, found in prominent human pathogens, are broadly distributed in nature. We show that zeta is a uridine diphosphate-N-acetylglucosamine (UNAG)-dependent ATPase whose activity is inhibited in vitro by stoichiometric concentrations of epsilon2 antitoxin. In vivo, transient expression promotes a reversible multi-level response by altering the pool of signaling purine nucleotides, which leads to growth arrest (dormancy), although a small cell subpopulation persists rather than tolerating toxin action. High c-di-AMP levels (absence of phosphodiesterase GdpP) decrease, and low c-di-AMP levels (absence of diadenylate cyclase DisA) increase the rate of persistence. The absence of CodY, a transition regulator from exponential to stationary phase, sensitizes cells to toxin action, and suppresses persisters formed in the disA context. These changes, which do not affect the levels of stochastic ampicillin (Amp) persistence, sensitize cells to toxin and Amp action. Our findings provide an explanation for the connection between -mediated growth arrest (with alterations in the GTP and c-di-AMP pools) and persistence formation.